Development of Dural Arteriovenous Fistulas After Cerebral Venous Sinus Thrombosis. Issue 1 (March 2016) - Micieli, Jonathan A.; Derkatch, Sheldon; Pereira, Vitor M.; Margolin, Edward A.
Abstract : Abstract: A 57-year-old man presented with papilledema due to partially recanalized dural sinus thrombosis and was treated with anticoagulation and acetazolamide. One year after treatment and resolution of his symptoms, he had an increase in his optic disc edema accompanied by headaches. Subsequent neuroimaging indicated development of arteriovenous fistulas resulting in cortical and deep venous reflux. Given the high risk of mortality from intracranial hemorrhage, the patient underwent urgent treatment with a liquid embolic agent, which resulted in the resolution of his optic disc edema. Our case is unique in that recurrence of bilateral optic disc edema led to discovery of the rare complication of dural arteriovenous fistulas developing after dural sinus thrombosis. Ongoing monitoring of patients after cerebral venous sinus thrombosis is, therefore, important.